In vitro transcription of mouse mammary tumor virus RNA into DNA. - Taylor, J M (1978)
The in vitro transcription of the B-type mouse mammary tumor virus RNA into DNA is similar to that obtained with certain C-type viruses: synthesis can be initiated on an RNA primer molecule approximately the size of a tRNA, and a unique linkage (rA-dC) exists between this primer and the DNA product.